Microleakage and characteristics of resin-tooth tissues interface of a self-etch and an etch-and-rinse adhesive systems - Tran, Xuan Vinh (Restor Dent Endod, 2021)
OBJECTIVES: This study was conducted to compare the microleakage and characteristics of the resin-tooth tissue interface between self-etch and etch-and-rinse adhesive systems after 48 hours and 3 months. MATERIALS AND METHODS: 40 extracted premolar teeth were randomly divided into 2 groups: 1-step self-etch adhesive system – Optibond™ All-In-One, and 2-step etch-and-rinse adhesive system - Adper™ Single Bond 2. Both groups were subjected to 500 thermocycles (5°C–55°C) before scanning electron microscope (SEM) analysis or microleakage trial at 48-hour and 3-month time periods. RESULTS: SEM images showed the hybrid layer thickness, diameter, and length of resin tags of the self-etch adhesive (0.42 ± 0.14 µm; 1.49 ± 0.45 µm; 16.35 ± 14.26 µm) were smaller than those of the etch-and-rinse adhesive (4.39 ± 1.52 µm; 3.49 ± 1 µm; 52.81 ± 35.81 µm). In dentin, the microleakage scores of the 2 adhesives were not different in both time periods (48 hours/3 months). However, the microleakage score of etch-and-rinse adhesive increased significantly after 3 months (0.8 ± 0.63 and 1.9 ± 0.88, p < 0.05). CONCLUSIONS: The self-etch adhesive exhibited better long-term sealing ability in dentin when compared to that of the etch-and-rinse adhesive. The greater hybrid layer thickness and dimensions of resin tags did not guarantee reliable, long-lasting sealing in the bonding area.